Photosynthesis of polypyyrole/ZnFe2O4-WO3 nanocomposite for biodiesel production - Chou-Yi Hsu; Zaid H. Mahmoud; Nargiza Kamolova; Khursheed Muzammil; Forat H. Alsultany; Salah Hassan Zain Al-Abdeen; Ehsan Kianfar (Fuel Processing Technology)
In this study, photolysis-free radical polymerization is successfully employed to synthesis a heterogeneous Polypyrrole/ZnFe2O4-WO3 nanocomposite. The photolysis technique was used UV irradiation with 15 W and 365 nm for reduction ferric, zinc and tungsten aqueous precursors for synthesis of metal oxides nanocomposite. The synthesized nanocomposite were characterized via X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and Raman spectrum and used it in transesterification of oil to investigate of the catalytic performance. The nanocomposite catalyst appeared high activity for esterification of olive oil creating from the increasing the diffusion between the reactant and product. Furthermore, the prepared nanocomposite catalyst could be easily recovered and efficiently reused for many times without considerable loss in its activity, also appeared results showed that PPy/ZnFe2O4-WO3 nanocomposite could be employed for the suitable and rapid biodiesel production. Depending on the experimental results, the optimum conditions with yield 94 % show at 1:14 oil/methanol ratio, 120 min, 55 °C temperature and 3 % catalyst dose. The obtained biodiesel appeared properties near to those of international standards of biodiesel. The product met international standards for key features, including density, viscosity and flash point, as well as, the catalyst appeared excellent reusability, keeping efficiency over multiple cycles with lower performance loss. These results proved the prepared catalyst as a cost-effective and sustainable catalyst for biodiesel production.